Characteristics of compositions in the audio format of the artist Khaled Mohamed Ali: مراد نصير أحمد حمدي (Al-Academy, 2020)
The research includes studying melodic and rhythmic properties, In the audio format for Iraqi musicians. The audio form is one of the important methodological forms in Arab music in general and Iraqi music in particular. It showcases its characteristics, features, internal form, and how important it is in Iraqi music. Addressed ((the systematic framework)) presenting the research problem and the need for it. Its importance, purpose and limitations of its research, which included music ((Khaled Muhammad Ali)) as a human limit to reveal its characteristics in the composition of the audio form. And define the terms included in the research. And included ((theoretical framework)) on three topics .. The first: composing. The second: the audio format. Third: Khaled Muhammad Ali. As for ((research procedures)) it was based on the descriptive analytical method. The “research community” included (20) samples of Khaled Muhammad Ali's audios. The sample was chosen from within this research. Turning to the research tool and the analytical standard. Then came ((Musical Analysis)) for the selected samples. Then the results of the analysis followed. And through which it was delivered to the conclusions based on the goals required in this research. Followed by a list of sources and an English language summary